A comprehensive mechanistic review insight into the effects of micronutrients on toll-like receptors functions. (February 2020) - Faghfouri, Amir Hossein; Zarrin, Rasoul; Maleki, Vahid; Payahoo, Laleh; Khajebishak, Yaser
Graphical abstract: Highlights: Some micronutrients can regulate TLRs gene expression dependent on dose, duration and cell type. NF-κB can be regulated by some micronutrients. Phosphorylation status of key enzymes in TLRs related signaling can be regulated by some micronutrients. Indirectly, zinc through zinc finger proteins can regulate TLRs signaling. Abstract: Toll-like receptors (TLRs) are the special proteins receptors for recognition of molecules related to the pathogens. In this way, TLRs and secreted cytokines as a result of TLRs activation are involved in the inflammation pathways. So far, in vivo and in vitro studies have demonstrated that micronutrients (vitamins & minerals) with a broad range of effects on body health, can regulate TLRs signaling pathways. Current review aimed at determining the possible mechanisms of micronutrient effects on TLRs functions. In the aspect of gene expression, micronutrients have inconsistent effects on mRNA level of TLRs which are dependent on time, dose and type of studied TLR. Also, some micronutrients affect gene expression of TLRs signaling mediators namely TLRs adaptors like Myeloid differentiation primary response 88 (MyD88). In the aspect of TLRs signaling pathways, nuclear factor‐κB (NF-κB) is an important mediator which is regulated by micronutrients. Also, the regulatory effects of micronutrients on phosphorylation reactions may be effective in the activation/inactivation of TLRs signaling mediators. In addition, zinc can regulate TLRs signaling indirectly via the zinc finger proteins which have contradictory effects on TLRs cascade. In conclusion, the relationship between micronutrients and TLRs signaling is complicated and depends on some known internal, external and genetic factors like form of studied micronutrient, cell type, TLR agonist, dose and time of exposure, inﬂammation, apoptosis, cell cycle, and environmental factors. Some unknown factors may be effective in TLRs response and as a result additional mechanistic studies are needed to elucidate exact effect of micronutrients on TLRs signaling.